Investigating Metacognitive Attitude of High School Biology Teachers - Zulfiani, Zulfiani; Herlanti, Yanti; Yunistika, Regiani (Jurnal Penelitian dan Pembelajaran IPA, 2020)
Teacher autonomy in learning is a part of professional accountability. The autonomy includes self-direct teaching as a reflection of the teachers’ metacognition in selecting learning strategies, monitoring the accuracy of strategy implementation, as well as evaluating the process. The metacognitive attitude directs the process of constructing knowledge and managing a classroom to meet the standard of the learning process. The objective of the present study is to describe the metacognitive attitude of Biology teachers. The survey research involved 57 Biology teachers in DKI Jakarta Province, Indonesia. The research instrument is the Metacognitive Awareness Inventory Teacher (MAIT) with Cronbach Alpha values r = 0.86. The results show that (1) the teacher's metacognitive attitude is high (mean 73.49), and (2) there was no correlation between metacognitive attitude with the school category or gender. This suggests the high performance of Biology teachers in autonomy especially in managing the Kurikulum 2013. This Kurikulum 2013 emphasizes student-centered learning which allows a variety of learning strategies that can be selected by the teacher to achieve a quality result. Male and female teachers both have equal opportunities in achieving their metacognitive attitudes, as well as the school category.